2010
DOI: 10.1016/j.jvs.2009.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term patency of small-diameter vascular graft made from fibroin, a silk-based biodegradable material

Abstract: Small-diameter fibroin-based vascular grafts have excellent long-term patency. Bone marrow-derived cells contribute to vascular remodeling after graft implantation. Fibroin might be a promising material to engineer vascular prostheses for small arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
193
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(200 citation statements)
references
References 38 publications
2
193
3
2
Order By: Relevance
“…Wu et al demonstrated rapid remodeling using a graft made of poly(glycerol sebacate), a fast-degrading elastomer, in a rat arterial implantation model having good patency. Natural proteins such as silk fibroin 15 and chitosan 16 have also been used as biodegradable materials for small-diameter arterial grafts, and showed long-term patency with favorable vessel remodeling. These materials have clear potential for small artery grafts, but further investigation in large animals with longer Representative electronic microscope images of poly(glycolic acid) (PGA) mesh fiber coated with poly(l-lactide-co-ε-caprolactone) (PLCL) and electrospun poly(lactic acid) (PLA) nanofiber.…”
Section: Biodegradable Polymersmentioning
confidence: 99%
“…Wu et al demonstrated rapid remodeling using a graft made of poly(glycerol sebacate), a fast-degrading elastomer, in a rat arterial implantation model having good patency. Natural proteins such as silk fibroin 15 and chitosan 16 have also been used as biodegradable materials for small-diameter arterial grafts, and showed long-term patency with favorable vessel remodeling. These materials have clear potential for small artery grafts, but further investigation in large animals with longer Representative electronic microscope images of poly(glycolic acid) (PGA) mesh fiber coated with poly(l-lactide-co-ε-caprolactone) (PLCL) and electrospun poly(lactic acid) (PLA) nanofiber.…”
Section: Biodegradable Polymersmentioning
confidence: 99%
“…Hemodynamics and antithrombotic indicators of the vascular prosthesis made of natural silk are better than vascular PTFE prosthesis [5].…”
Section: Implantsmentioning
confidence: 91%
“…5,6 We have already reported excellent results for the development of small-diameter vascular grafts made from SF. [7][8][9][10] These novel vascular grafts made from SF (length: 8 mm; internal diameter: 1.5 mm) improved the patency of the graft remarkably, that is, more than 85% patency remained after 1 year of implantation in rat abdominal aorta. 8,9 Although the SF fiber is superior in patency compared with other synthetic materials used in grafts, it is difficult to use the SF alone as an artificial vascular graft because of its poor mechanical stability, such as its low yielding property and weakness against bending.…”
Section: Introductionmentioning
confidence: 91%
“…[7][8][9][10] These novel vascular grafts made from SF (length: 8 mm; internal diameter: 1.5 mm) improved the patency of the graft remarkably, that is, more than 85% patency remained after 1 year of implantation in rat abdominal aorta. 8,9 Although the SF fiber is superior in patency compared with other synthetic materials used in grafts, it is difficult to use the SF alone as an artificial vascular graft because of its poor mechanical stability, such as its low yielding property and weakness against bending. In contrast, it is known that several types of polyurethanes (PUs) are satisfactory materials in solving thrombosis and operability problems because of their excellent elastic properties and their biocompatible, microporous structure.…”
Section: Introductionmentioning
confidence: 91%